Immune response, smoking, and lung cancer: a systematic review - V. Yu. Buslaev; A. V. Minin; M. V. Katanakhova; A. V. Shabaldin (Фундаментальная и клиническая медицина)
Here we review the role of innate and adaptive immunity at ascending lung cancer stages in smoking and non-smoking patients. T cell activity and the expression of pro-inflammatory cytokines were found to be elevated in smokers. As a consequence, smoking has been identified as a significant risk factor promoting lung carcinogenesis. Further experimental research in this area will allow the development of novel diagnostic approaches, including circulating biomarkers and personalised medicine.